From CD4-Based Initiation to Treating All HIV-Infected Adults Immediately: An Evidence-Based Meta-analysis - Song, Aixin; Liu, Xinchao; Huang, Xiaojie; Meyers, Kathrine; Oh, Djin-Ye; Hou, Jianhua; Xia, Wei; Su, Bin; Wang, Ni; Lu, Xiaofan; Xia, Huan; Yang, Xiaodong; et al. (Frontiers in Immunology, 2018)
Abstract Background The World Health Organization (WHO) Consolidated antiretroviral therapy (ART) guidelines set the CD4+ T-cell count threshold to 500 cells/mm3 in 2013, and 2015 guidelines recommend treating all HIV-infected adults regardless of their CD4+ T-cell count. To inform the decision-making around ART guidelines for people living with HIV, we systematically reviewed the literature to estimate differences in clinical benefits between individuals starting treatment with baseline CD4+ T-cell counts ≥500 cells/mm3 (early initiation) as compared to <500 cells/mm3 (deferred initiation). Methods We systematically searched the electronic databases and abstracts for randomized controlled trials (RCT) and observational studies. Outcomes were mortality, AIDS progression, AIDS or death, immunologic recovery and virologic suppression. We pooled data across studies and performed analyses of effect sizes. Results We identified 13 studies comparing early and deferred treatment. The pooled risk ratio (RR) of mortality of 11 observational studies was 0.90 (95% CI 0.82-0.99), with moderate heterogeneity (I2=53%). The pooled RR for progression to AIDS from two observational studies was 0.77 (95% CI 0.47-1.24). Five observational studies found a pooled RR of death or AIDS of 0.94 (95% CI 0.93-0.95). For the outcome of immunologic recovery, defined as CD4+ T-cell counts reaching at least 800 cells/mm3 after ART, one observational study found early initiation of ART had an HR (hazard ratios) of 2.39 (95% CI 1.93-2.96). The pooled RR of viral suppression (a viral load <50 copies/ml) after 9 months from one cohort was 1.04 (95% CI 0.99-1.09). Conclusions Mortality risk and risk for AIDS appear to be reduced among people living with HIV with early initiation of ART, based on current WHO guidelines, as compared to those with deferred initiation of ART (<500 cells/mm3).